Office managers skills and it’s impact on the effectiveness of time management A survey of a sample of departments managers in the institutes and faculties at the middle technical university - محمد رائدة مال الله (Journal of Economics and Administrative Sciences, 2017)
The objective of this study is to highlight the skills of office managers and it’s impact on the effectiveness of time management in the institutes and faculties of middle technical university and a group of cognitive and practical aims. The managers skills forms mthe modern trend and the main source to provide organizations with highly skilled managers with distinctive performance and because of the sharp changes in the environment which today’s organizations works in it , business organizations generally and managers especially realise the importance of time management and it’s role in achieving competitive advantage . The problem of this study raised from this point which reflect the extent of departments managers realisation in the surved organizations to the great impact of skills on the effectiveness of time management . According to this problem,and to explain the relationships among research variables,we put two main hypothesis and ten secondary hypothesiss. We used questionnaire as a tool to collect data and information related with research variables and it was prepared according to pre tested measures using Lechert scale . We choose an intentional sample consists of 40 office managers in some technical institutes and faculties in Baghdad city. The main results refers that the skills of office managers (the sample) correlate with and impact greatly on the effectiveness of time management especially when it’s accompanied